2015
DOI: 10.1515/ausae-2015-0009
|View full text |Cite
|
Sign up to set email alerts
|

Elemental profile of edible mushrooms from a forest near a major Romanian city

Abstract: We determined the elemental profile of 16 edible mushroom species from the Făget Forest, near Cluj-Napoca, and of 12 species from the Apuseni Mountains. Oneway ANOVA showed no difference in the elemental content of mushrooms when the two regions were compared. Some species accumulated high amounts of trace elements, i.e. Boletus edulis (Ag, S, Zn), Macrolepiota procera (Cu), Lactarius volemus (Co), Russula emetica (Mn), Armillariella mellea, and Chantarellus cibarius (Cr). The cadmium content was the highest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
(32 reference statements)
1
5
0
Order By: Relevance
“…This metal concentration in the stipe was the highest in L. semisanguifluus, 159 mg kg -1 , while L. deliciosus had the lowest, 82 mg kg -1 . Zsigmond et al 18 obtained similar results who examined the inorganic composition of many mushrooms, among which the species L. deliciosus, and the obtained results are similar to results of this study, except that the concentration of aluminum in the cap (52.4 mg kg -1 ) is higher than in the stipe (31.3 mg kg -1 ). Sarikurkcu et al 20 reported lower concentrations of Al in L. sanguifluus (63 mg kg -1 DW).…”
Section: O N L I N E F I R S Tsupporting
confidence: 89%
“…This metal concentration in the stipe was the highest in L. semisanguifluus, 159 mg kg -1 , while L. deliciosus had the lowest, 82 mg kg -1 . Zsigmond et al 18 obtained similar results who examined the inorganic composition of many mushrooms, among which the species L. deliciosus, and the obtained results are similar to results of this study, except that the concentration of aluminum in the cap (52.4 mg kg -1 ) is higher than in the stipe (31.3 mg kg -1 ). Sarikurkcu et al 20 reported lower concentrations of Al in L. sanguifluus (63 mg kg -1 DW).…”
Section: O N L I N E F I R S Tsupporting
confidence: 89%
“…In addition, it can be concluded that this parameter was increasingly used in studies over the last decade of the analysis. In the research of many of the authors, they stressed the need to assess the Hazard index (HI) Falandysz et al 2002a;Falandysz et al 2003a;Falandysz et al 2003b;Zsigmond et al 2015 Hazard quotient (HQ) Zsigmond et al 2015 Provisional tolerable weekly intake (PTWI) Blanuša et al 2001;Çayir et al 2010;Chudzyński et al 2009;Chudzyński et al 2011;Dimitrijevic et al 2016;Drewnowska et al 2014;Dryżałowska and Falandysz 2014;Falandysz and Drewnowska 2015;Frankowska et al 2010;García et al 2009;Giannaccini et al 2012;Gucia et al 2012;Gursoy et al 2009;Komárek et al 2007;Krasińska and Falandysz 2015;Krasińska and Falandysz 2016;Larsen et al 2002;Maćkiewicz and Falandysz 2012;Malinowska et al 2004;Miklavčič et al 2013;Mirończuk-Chodakowska et al 2013;Ostos et al 2015;Ouzouni et al 2007;Petkovšek and Pokorny 2013;Rudawska and Leski 2005a;Sarikurkcu et al 2011;Sarikurkcu et al 2012;Stefanović et al 2016b;Svoboda et al 2006 Reference dose (RfD) Chudzyński et al 2009;Chudzyński et al 2011;Drewnowska et al 2014;Dryżałowska and Falandysz 2014;Falandysz ...…”
Section: Resultsmentioning
confidence: 99%
“…The publications whose authors assessed the health risks arising from the consumption of contaminated mushrooms (i.e. with heavy/toxic metals) are also listed according to the different indices (Falandysz and Drewnowska 2015;Melgar et al 2014;Zsigmond et al 2015). This article contains a bibliometric analysis of 200 European publications about the concentrations of selected elements in mushrooms that were published between 2001 and 2016.…”
Section: Introductionmentioning
confidence: 99%
“…China is the main producer of cultivated, edible mushrooms. Collecting wild edible mushrooms for consumption is widely practiced in many countries, including Romania [9,10]. The consumption of mushrooms is expected to increase, since consumers are becoming aware of the helpful benefits brought in the diet [11].…”
Section: Introductionmentioning
confidence: 99%